Strengthening Penta Helix Collaboration for Enhancement Quality of Education - Husnah, Wabilia; Ismail Muzakir , Muhammad Athar; Chairu, Trida; Choiruddin; Ardianti, Eka Aulia; Karnadi; Radiwan (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This study aims to reconstruct synergy between all penta helix actors, to improve educational quality. To answer this problem, we use qualitative research with a case studies approach in Riau Islands province, Bangka Belitung Islands province, Bali province, and Gorontalo province. This study discovered synergy between all Penta Helix actors, including central government, regional government, business sector, education sector, society, and media. However, there are several barriers to implementing this synergy. As a result, this study recommends strengthening synergy between institutions at the central level of government (Ministry of Home Affairs and Ministry of Education, Culture, Research, and Technology), Regional Apparatus Organizations (OPD) in provincial and district governments, and all Penta Helix actors. The implications of this study could be used to improve education quality in Indonesia.